КИИА ОД ПОЧЕТОКОТ ДО 70-ТИТЕ ГОДИНИ НА XX ВЕК (Annual of the Faculty of Philosophy in Skopje, 2009)
People's Republic of China has a great role in the modem world. Itshistory in XX century was full of bloody events in the struggle for eliminationof foreign influence. As weil as, in China were fighting long wars which claimeda lot of death-toll. In this period many persons were distinguished themselvesand leaved their mark on the contemporary history of the PR China. PR Chinaduring this period had performed many reforms which were reflected oneconomic situation in the country especially this was typically in the periodafter the Second World War. At the same teme, China was in active foreignpolitics for breakout in the external world.
Keywords: PR CHINA; CIVIL WAR; MAO ZEDONG; SUN; YAT-SEN; KUOMINTANG